Quality assurance of the linear accelerator device using Star Track and Perspex - Rejah, Dr. Basim Khalah (Iraqi Journal of Physics, 2019)
In this study, the quality assurance of the linear accelerator available at the Baghdad Center for Radiation Therapy and Nuclear Medicine was verified using Star Track and Perspex. The study was established from August to December 2018. This study showed that there was an acceptable variation in the dose output of the linear accelerator. This variation was ±2% and it was within the permissible range according to the recommendations of the manufacturer of the accelerator (Elkta).